When Actions Speak Louder Than Words - Justine McGovern (SAGE Publishing, 2016)
Through the lens of a study exploring dementia care partnering, the purpose of this methods article is to focus on the role of artifacts and embodied data in data collection. In addition, it illustrates how to use a range of data collecting methods. The article identifies benefits of additional data collecting methods to research and care. These include the need to expand data collecting methods beyond spoken word, integrate a range of data collecting approaches into research courses across disciplines, increase support of qualitative research, and advocate for greater inclusivity in research. Data collecting approaches can also have implications for quality of life among persons often excluded from research-building endeavors. They can contribute to the unfolding of new findings, which can influence care practices.